Export-Based MSME Internationalization Development Strategy: Digital Marketing and Digital Leadership in Indonesia - Mala , Iva Khoiril; Mukhlis, Imam; Fulgentinus Danardana Murwani; Choirul Anam (Asian Journal of Management Analytics, 2024)
This research aims to investigate export-based MSME development strategies with a focus on the role of digital marketing and digital leadership in Indonesia. The research method used is in-depth interviews with SMEs owners who have succeeded in developing their export markets using digital platforms. The research results show that using digital marketing, such as social media and search engine optimization, is very important to increase the visibility and competitiveness of SMEs in the global market. Digital leadership from SMEs owners also plays a key role in driving innovation and adaptation to global market changes. These findings have important implications for SMEs owners and other stakeholders in developing effective strategies to face challenges and exploit opportunities in export market expansion.